Intraparenchymal cerebellar capillary hemangioma in a 32-year-old man: a case report - Wardhana, Dewa Putu Wisnu; Awyono, Steven; Lauren, Christopher; Muhammad Rosyidi, Rohadi; Saputra, Herman (Frontiers in Surgery, 2023)
The authors present an unusual case of a 32-year-old adult male with a capillary hemangioma, which developed within the left cerebellar parenchyma. The histopathological examination reveals a mass mostly formed by the proliferation of capillaries, lined by a layer of flat-plump endothelial cells, some branching and dilating large capillaries, forming a lobulated structure separated by fibrocollagenous connective tissue. Immunohistochemistry examination with CD31 and S100 was positive on the endothelial and stromal cells, respectively, and negative S100 on the endothelial cells. Although rare, capillary hemangioma should be one of the differential diagnoses for diagnosing intra-axial lesions in the cerebellar region. Confirmation of the histopathological characteristic is necessary to determine the diagnosis of capillary hemangioma and exclude other differential diagnoses.